2014
DOI: 10.1002/zoo.21191
|View full text |Cite
|
Sign up to set email alerts
|

Ascarisspp. andCapillaria caudinflatainfections in captive-bred crested ibis (Nipponia nippon) in China

Abstract: Crested ibis (Nipponia nippon), an endan gered native bird, was called the "precious stone" of oriental birds. N. nippon was considered a critically endangered species in the IUCN Red List of Threatened Species and a first-class national protected animal in China. The Chinese government had exerted considerable effort to protect the N. nippon population. An effective approach to increase the number of these birds was captive breeding. However, several pathogens, including parasites, could jeopardize the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…By analyzing the genomes of 57 historic and 8 modern samples, a recent study revealed ancestral loss of genetic variation and high deleterious mutation owing to genetic drift and inbreeding depression in current populations [32]. There have been a growing number of reports regarding various infections [33,34,35,36] and high mortality [29,33] in this bird, indicating frequent threats from pathogens and undetermined fitness. However, there has not yet been any large-scale genetic assessment on Nini populations.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the genomes of 57 historic and 8 modern samples, a recent study revealed ancestral loss of genetic variation and high deleterious mutation owing to genetic drift and inbreeding depression in current populations [32]. There have been a growing number of reports regarding various infections [33,34,35,36] and high mortality [29,33] in this bird, indicating frequent threats from pathogens and undetermined fitness. However, there has not yet been any large-scale genetic assessment on Nini populations.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have carried out experimental procedures or statistical analyses to prove the cross-transmission of parasites between captive and free-ranging individuals [ 43 , 44 ]. The majority of recent studies simply describe parasites in fecal samples or on postmortem examination [ 27 , 45 – 47 ]. This review identifies parasite species that have been reported in both zoo birds and free-ranging avifauna.…”
Section: Resultsmentioning
confidence: 99%
“…In captive breeding centers in China, more than half of Asian crested ibis ( Nipponia Nippon ) were positive for Ascaris spp. and C. caudinflata by coprological examination [ 45 ]. Zhang at al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, previous research related to the crested ibis focused on external factors such as viruses, bacteria, and parasites that influence survival, and incorporated microsatellite markers, major histocompatibility complex loci, and defensins that only provide limited genomic information for the development of particular measures for species conservation (Zhang et al. 2004, 2006, 2015; He et al. 2006; Xi et al.…”
Section: Introductionmentioning
confidence: 99%